Utilizing Sewage Sludge Slag, a By-Product of the Circulating Fluidized Bed Combustion Process, to Efficiently Remove Copper from Aquatic Environment - Tomasz Kalak; Yu Tachibana (Energies, 2023)
Currently, one of the greatest threats to the aquatic environment is industrial wastewater containing heavy metals and other toxic substances. Hence, it seems necessary to search for ecological and cheap technologies for removing metals from wastewater. In this research, slag was used as waste obtained in the circulating fluidized bed combustion technology (CFBC), which is considered to be a modern, clean, and very effective method of incineration of municipal sewage sludge. The physicochemical properties of the waste material were characterized using selected analytical techniques. Next, the processes of adsorption of Cu(II) ions on slag in aqueous solutions were investigated. The results showed a high metal removal efficiency of 98.8% at pH 1.8 and slag dosage 5 g/L. Numerous studies have demonstrated that high process efficiency at a level of at least 90% is attainable. Based on the Langmuir equation, the maximum adsorption capacity was calculated to be 70.3 mg/g. Kinetic analysis revealed that the process fits better into the pseudo-second-order reaction model and the Freundlich isotherm. The intraparticle diffusion model was considered as a rate-controlling step for Cu(II) adsorption. In summary, the slag waste produced in the CFBC technology seems to be a highly effective adsorbent for potential use in adsorption processes to remove heavy metals from the aquatic environment. This solution is in line with the current European ‘zero waste’ strategy and the assumptions of a sustainable development economy.